2011
DOI: 10.4304/tpls.1.12.1797-1803
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Focused and Unfocused Written Corrective Feedback on Grammatical Accuracy of Iranian EFL Learners

Abstract: Abstract-This study aimed at investigating whether direct focused corrective feedback and direct unfocused corrective feedback caused any differential effects on the accurate use of English articles by EFL learners across two different proficiency levels (low and high). The participants were divided into low and high proficiency levels by administering a TOEFL test. Then, sixty learners in each proficiency level formed two experimental groups and one control group, 20 learners in each group. One experimental g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 22 publications
0
21
2
Order By: Relevance
“…As WCF is given off-line, unlike oral feedback, which needs to be given during communication and therefore cannot be attended to so easily, it is even more likely to be detected (Bitchener, 2012;Ellis, 2003;Polio, 2012). These theoretical bases help explain why recent studies of written feedback, which have focused on eliminating the methodological problems of earlier studies (identified, for example, in Bruton, 2009;Ferris, 2003), have found evidence for the positive effects of feedback on language acquisition (Bitchener andKnoch, 2008, 2010;Ellis, Sheen, Murakami, and Takashima, 2008;Farrokhi and Sattapour, 2011;Hyland, 2011;Hanaoka and Izumi, 2012;Shintani, Ellis, and Suzuki, 2014;Van Beuningen, De Jong, and Kuiken, 2012).…”
Section: Introductionmentioning
confidence: 92%
“…As WCF is given off-line, unlike oral feedback, which needs to be given during communication and therefore cannot be attended to so easily, it is even more likely to be detected (Bitchener, 2012;Ellis, 2003;Polio, 2012). These theoretical bases help explain why recent studies of written feedback, which have focused on eliminating the methodological problems of earlier studies (identified, for example, in Bruton, 2009;Ferris, 2003), have found evidence for the positive effects of feedback on language acquisition (Bitchener andKnoch, 2008, 2010;Ellis, Sheen, Murakami, and Takashima, 2008;Farrokhi and Sattapour, 2011;Hyland, 2011;Hanaoka and Izumi, 2012;Shintani, Ellis, and Suzuki, 2014;Van Beuningen, De Jong, and Kuiken, 2012).…”
Section: Introductionmentioning
confidence: 92%
“…As the focus of the present review article is grammatical correction, the feedback concerning grammar improvement is reviewed and discussed. Teacher corrective feedback that involves grammar correction is form-focused feedback (Farrokhi & Sattarpour, 2011;Ismail et al, 2008;Razali & Jupri, 2014;Sheen et al, 2009). According to past studies, this type of feedback can be divided into two groups: focused and unfocused.…”
Section: Teacher Corrective Feedbackmentioning
confidence: 99%
“…The latter one concerns global errors when teachers correct all grammatical errors found in students' written work. Scholars (Eslami, 2014;Farrokhi & Sattarpour, 2011;Ismail et al, 2008;Sheen et al, 2009) state that focused feedback type is more effective because students can focus on one small error at a time which can eventually help them avoid making that error in the future. A great number of studies reported the effectiveness of teacher written feedback.…”
Section: Teacher Corrective Feedbackmentioning
confidence: 99%
“…Unfocused feedback, on the other hand, involves the teacher giving feedback on all errors in the student's work. According to the results of a number of studies, focused feedback is highly beneficial to students (Bitchener, 2008;Bitchener & Knoch, 2008;Farrokhi & Sattarpour, 2011;Sheen, 2007;Sheen, Wright, & Moldowa, 2009;Shintani & Ellis, 2013). Nonetheless, as McGrath (2015) pointed out, its effectiveness may be questionable in courses in which students only produce two or three pieces of writing in a semester.…”
Section: Jones and Tang: Teacher And Student Perspectives On Written Fementioning
confidence: 99%
“…Since that claim was made, numerous studies have shown that corrective feedback can have positive and lasting effects. However, these have all dealt with focused feedback and have centered around improving a single language point (Bitchener, 2008;Bitchener & Knoch, 2008;Farrokhi & Sattarpour, 2011;Sheen, 2007;Sheen, Wright, & Moldowa, 2009;Shintani & Ellis, 2013). Far fewer studies have made similar claims about unfocused feedback, though Van Beuningen, De Jong, & Kuiken, (2012) found that long term gains in grammatical accuracy, content, and organization could also be made through unfocused feedback.…”
Section: Usefulness Of Feedbackmentioning
confidence: 99%